Synthesized and Characterization TiO2-AlLiH4 Nanostructure for Photocatalytic Activity Application for Removal the Residue of Hydrocarbons in Environment - Al Salih, Moatasem; Abed, Riyad E. (Journal of Petroleum Research and Studies, 2022)
The novel approach includes The sol-gel technique was used to make titanium dioxide nanoparticles and then for photodegradation Benz[a]anthracene a crystalline, aromatic hydrocarbon, as a trial sample of the residue of hydrocarbons in environments close to oil refining facilities and oil fields, methods, the bandgap was modified by solid-state reaction with Lithium aluminium hydride (AlLiH4) reductive compounds. The optical properties were measured using a UV-visible spectrophotometer (Absorbance (A), energy bandgap (Eg), and absorption coefficient (α). TiO2 and TiO2- solid-state reaction showed a clear blue shift of the absorption bandgap which were (2.8ev, 2.7ev, 2.25ev, 2.0ev) to) TiO2, calcination TiO2-AlLiH4 (500C°) then TiO2 -AlLiH4 (750 C°)) respectively. The structure of prepared TiO2 Nanopowders was identified using XRD, Distribution of particle size varied significantly compared to the Sheerer formulation predicted crystallite size (D). which was in a good accordant compared with ASTM results, the particle size and their distribution were characterized using (AFM). To the surface forms and compositions diameters of nanoparticles) SEM) was implemented. The microanalysis of energy scattering X-ray (EDX) was used to examine the chemical makeup of the entire samples. Using UV-Vis spectrophotometry, the photocatalytic response was examined. The photocatalyst impact on the benz[a]anthracene decomposition rate by using catalyst TiO2- and solid-state (TiO2-NaBH4 (550,750)) and (TiO2-AlLiH4 (500,750 C°). A photocatalytic effect is the catalyst's influence on the catalyst. Using the constant weight of the catalyst and benz[a]anthracene The most effective weight was found (1*10-4 M).